"Look like the innocent flower, but be the serpent under't": Mimicking behaviour of growth-oriented terrorist organizations - Ulrich Hendel (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
This paper examines the interaction between a growth-oriented terrorist organization and an uninformed government based on a two-period signaling game. The terrorists, taking into account the government's counter-terrorism response to first period attacks, gain additional manpower from successful attacks and choose their strategy to maximize the available manpower at the end of period 2. The government tries to infer the terrorist organization's size from the terrorists' attack choice it observes in period 1 and adjusts its second period counter-terrorism spending according to the perceived threat of terrorism. Combining the signaling game and organizational growth approaches of previous contributions, this paper shows that, if a terrorist group follows a growth strategy, it has an incentive to appear weaker than it is by mimicking the behaviour of a smaller organization. Furthermore, depending on its beliefs about the extent of the terrorist threat it can be optimal for a government to spend more on second period counter-terrorism measures if it is not attacked than if it were attacked. The behaviour of contemporary terrorist groups suggests that the assumptions of a growth strategy and mimicking behaviour are justified.
urn:nbn:de:bvb:19-epub-13998-3
Keywords: H56; C72; D82; 330; terrorism; counter-terrorism; game theory; Terrorismus; Organisation; Kriminalpolitik; Signalling; Nichtkooperatives Spiel; Theorie